Five modern Japanese novelists - Keene, Donald (Columbia University Press, 2003)
A superb introduction to modern Japanese fiction as well as a memoir of his own love affair with Japanese literature and culture, this volume consists of chapters on five modern Japanese novelists whom Donald Keene knew personally: Yasunari Kawabata, Yukio Mishima, Jun'ichiro Tanizaki, Ryotaro Shiba, and Kobo Abe. Each chapter opens with a vignette describing Keene's personal encounters with these famous men, blending his autobiographical observations with literary and cultural analysis.